Age as risk factors associated in the genesis of uterovaginal prolapse (UVP) - Pandit, Upendra; Malla, Dibya Shree; Sharma, Paban Kumar (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aim: To find out the relationship between utero-vaginal prolapse (UVP) and first vaginal birth at younger age <22 years and to identify single most frequently occurred risk factor in study group. Method: A hospital based descriptive comparative study was carried out in 200 women of age 40- 60 years in two hospitals. One hundred women with UVP were enrolled as case (Group I) and 100 women with similar parity and age group but admitted for other reasons than prolapse were enrolled as comparative group (Group II). Relationship was observed between two groups in their age at first vaginal birth, duration of labour, family history, smoking habit, menopause and BMI. Results: Cases of UVP occurred in younger <22 years at first vaginal birth than comparable group (OR 3.41, 95% CI 1.74-6.72, P = 0.00009). The mean of duration of labour pain was 30.85±26 vs 18.87±21.3 (P=0.006) hours in Group I and Group II respectively. There was increased risk of UVP in women who had family history (OR 2.35; 95% CI 1.16-4.78, P= 0.01). Conclusion: Single most frequently identified risk factor was young age <22 years at first vaginal birth. DOI: http://dx.doi.org/10.3126/njog.v3i2.10832 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 48-50